Assessment of simplified and advanced models for shear resistance prediction of stirrup-reinforced concrete beams. (1st May 2019) - Olalusi, Oladimeji Benedict; Viljoen, Celeste
Highlights: Shear strength predictions from existing models differ from experimental results. Predictions by MCFT(R2k) and CCC bear the closest comparison to experimental results. Design values of current shear design provisions compare well, except for Eurocode 2. Eurocode 2 shear design formulation may be uneconomical at low levels of stirrups. Abstract: An accurate method for predicting shear strength for reinforced concrete beams is paramount since shear failure is catastrophic and can lead to grave consequences. Different standards and guidelines use different models for shear resistance predictions. Their stipulations on shear design differ considerably from one another, resulting in different design procedures and safety performance. This contribution assessed the mean and design value predictions of shear models for beams with shear reinforcements in currents codes and published technical literature. The models investigated includes the EC2 VSIM shear model, the ACI 318 (2011) shear model, the Fib Model Code 2010 (MC-10 (III)) shear model, the best-estimate prediction by Modified Compression Field Theory (MCFT) based analysis program Response 2000 (R2k) and the Compression Chord Capacity model (CCC). The mean and design value predictions from the various methods are compared to one another and to experimental results, over the parametric range of shear reinforcement, concrete strength and beam depth. The assessment revealed that the mean value predictions of the different models differ considerably from one another and from experimental observations. The mean value predictions from MCFT (R2k) and CCC predictions bear the closest comparison to that of the experimental observations for the range of shear reinforcement ρ w f ywm investigated. The mean value predictions of the EC2 VSIM was shown to significantly underpredict capacity for slightly shear-reinforced concrete beams. The shear method produced the most conservative mean value predictions out of all the methods investigated at shear reinforcement ρ w f ywm ≤ 1 M P a . The design value analysis revealed that the design values of the various shear design methods compare well, except for EC2 VSIM at low levels of design shear reinforcement ( ρ w f ywd ≤ 1 M P a ).